Violencia intrafamiliar Colombia en cuarentena: ¿encerrados con el enemigo? (2021)
The COVID-19 pandemic has caused a disruptive change in the course of the economy, social relationships and people's daily dynamics due to the quarantine-type isolation measures implemented to mitigate the spread of the virus. In this sense, it would be expected that domestic violence is affected by lockdown, economic stress and a greater coexistence between victims and perpetrators. This document analyzes the effect of quarantines on complaints of domestic violence in Colombia registered in the SIEDCO of the 'Policía Nacional'. Using a difference-in-difference model, it is found that the isolation measures caused a reduction of 1.05 weekly complaints per 100,000 inhabitants on average per municipality, representing a variation of -47.71% compared to the control group in the pre-quarantine period. In the 13 main cities of the country there is a fall of 3.34 weekly complaints per 100,000 inhabitants on average per main city, which represents a variation of -33.74% compared...